(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
In Ayurveda, Prakriti represents an individual’s inherent constitution, which remains stable throughout life. Similarly, blood groups are genetically inherited and do not change. Both Prakriti and blood group are innate and unchanging attributes, suggesting a potential relationship between the two. Objective: To investigate the correlation between Dehaprakriti and blood group among individuals, hypothesizing that a noteworthy association may exist between these two fixed traits. Methods: An observational study was conducted with a sample of 500 individuals. The assessment included both subjective and objective measures. Subjective Assessment: Each participant’s Prakriti was determined using a self-assessment questionnaire developed by Kishore Pattawardhan and Sharma. Objective Assessment: Each participant’s blood group was recorded following Prakriti determination. The data were then subjected to statistical analysis using chi- square tests to examine correlations between Prakriti types and blood groups. Results: The chi-square analysis revealed a significant association between Dehaprakriti and blood group, with a p-value of less than 0.05. However, no single Prakriti type was found to correspond exclusively with a specific blood group, as most blood groups appeared across multiple Prakriti types. Conclusion: Although a significant correlation exists between Dehaprakriti and blood group, the study concludes that blood groups cannot be used as definitive markers for categorizing dominant Prakriti. Further studies with larger samples and diverse populations are recommended to explore this relationship in greater detail.